2014
DOI: 10.1016/j.sjopt.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Lacrimal canaliculitis

Abstract: Canaliculitis is an uncommon, often misdiagnosed diagnosis because canaliculitis can mimic many other common ocular conditions. Canaliculitis should be appropriately diagnosed and treated to avoid recurrent inflammation and possible obstruction of the upper portion of the lacrimal system. This review will serve as a concise resource to aid in diagnosis and provide updated management options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…In our study, the most common isolate of plug-related canaliculitis is P. aeruginosa , followed by P. acnes and Staphylococcus sp. The low incidence of the isolation of Actinomyces in the current study may be due to its fastidious nature or the propensity for a polymicrobial aetiology of canaliculitis which makes it hard to grow from routine conjunctival eye swabs 17. Innoculums placed on blood agar, chocolate agar, Sabouraud dextrose agar and PD Plus/F blood culture bottle (Beckton, Dickinson & Co., Franklin Lakes, New Jersey, USA) and incubated anaerobically have been reported to improve the detection rate of Actinomyces sp 3 20 21.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In our study, the most common isolate of plug-related canaliculitis is P. aeruginosa , followed by P. acnes and Staphylococcus sp. The low incidence of the isolation of Actinomyces in the current study may be due to its fastidious nature or the propensity for a polymicrobial aetiology of canaliculitis which makes it hard to grow from routine conjunctival eye swabs 17. Innoculums placed on blood agar, chocolate agar, Sabouraud dextrose agar and PD Plus/F blood culture bottle (Beckton, Dickinson & Co., Franklin Lakes, New Jersey, USA) and incubated anaerobically have been reported to improve the detection rate of Actinomyces sp 3 20 21.…”
Section: Discussionmentioning
confidence: 80%
“…Actinomyces israelli is often considered as the most common isolated microorganism in primary canaliculitis 17. Some recent studies demonstrate greater rates of infection with Streptococcal and Staphylococcal spp as causative microorganisms 9 18.…”
Section: Discussionmentioning
confidence: 99%
“…Though, on culture, no growth was seen as culturing of Actinomyces is difficult due to its anaerobic nature. 1 It was concluded that concretions which do not grow characteristic findings of Actinomyces or other organism may simply be sterile necrotic tissue and debris.…”
Section: Case Reportmentioning
confidence: 99%
“…Canaliculitis is an inflammation of the lacrimal canaliculi caused by infection or as a complication of punctal plug insertion. 1 It is often misdiagnosed leading to a delay in diagnosis. 2 Canaliculitis is an uncommon condition, often can mimic many other common ocular conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation